The simultaneous application of optimum network reconfiguration and distributed generation sizing using PSO for power loss reduction - Dahalan, W.M.; Mokhlis, Hazlie; Bakar, A.H.A.; Jamian, J.J. (Optymalizacja rekonfiguracji sieci elektroenergetycznej i rozmiarów generatorów rozproszonych w redukcji strat energetycznych - zastosowanie algorytmu PSO, 2013)
The utilization of Distributed Generation (DG) sources in Distribution Power system is indeed vital as it is capable of solving problems especially pertaining to power losses due to an increasing demand for electrical energy.The location and optimal size of DG has become a prominent issue for the network to have lower power losses value. In order to reduce unnecessary power losses, the use of a combination reconfiguration method and DG units can assist the system to obtain optimal power loss in the network distribution. The primary idea is to have the reconfiguration process embedded with Distributed Generation (DG) and being operated simultaneously to reduce power losses and determine the optimal size of DG by using Particle Swarm Optimization (PSO). The objective of this paper is to focus on reducing the real power losses in the system as well as improving the voltage profile while fulfilling distribution constraints. The simulation results show that the use of simultaneous approach has resulted the lower power losses and better voltage profile of the system. A detail performance analysis is carried out on IEEE 33-bus systems demonstrate the effectiveness of the proposed methodology.